Acting knowingly: effects of the agent's awareness of an opportunity on causal attributions. (1st October 2016) - Hilton, Denis J.; McClure, John; Moir, Briar
ABSTRACT: According to difference-based (e.g. counterfactual/covariational) models of causal judgement, the epistemic state of the agent should not affect judgements of cause. Four experiments examined opportunity chains in which a physical event (distal cause) enabled a subsequent proximal cause to produce an outcome. All four experiments showed that when the proximal cause was a human action, it was judged as more causal if the agent was aware of his opportunity than if he was not or if the proximal cause was a physical event. The first two experiments showed that these preferences could not be explained in terms of differences in perceived conditional probability (whether from the observer's or the agent's point of view), social controllability or perceptions of the causal sequence as forming a single unit. The third experiment showed that awareness affected the perceived deliberateness with which the action brought the outcome about but not its perceived voluntariness. The fourth experiment showed that when the outcome was intended, the perceived deliberateness of the agent's action was a plausible mediator of the effect of awareness of opportunity on causal preference. We conclude that awareness of the opportunity allows inferences about the deliberate production of the outcome when the action is voluntary, which in turn influence causal judgements.